Analisis Multivariat Ukuran Tubuh Sebagai penduga Hubungan Kekerabatan subpopulasi sapi pesisir Di sumatera Barat - Sarbaini Sarbaini (Universitas Andalas, 2007)
The discriminate function and canonical correlation analysis were carried out in order to differentiate between subpopulations, and to determine the discriminate variables which may contribute on the differentiation of the three Pesisir cattle subpopulations in West Sumatra. Around 528 of Pesisir cattle's were as sample. They were distributed in three subpopulations in West Sumatra: Pesisir Selatan, Padang Pariaman, and Agam districts. Body measurement data were collected for body weight, body length, withers height, hip height, chest width, chest depth, chest girth, hip width, head length, and head width. The data were statistically analyzed by using discriminate function. The results of the study found that the Pesisisr cattle growing in Padang pariaman showed very different in body measurement with those growing in Agam and Pesisir Selatan subpopulation. The results also indicated that withers height, hip height, head width, body weight, and head length were the most importance body measurement to differentiate amongst the Pesisir cattle population in west sumatra.